Les politiques de l’écriture migrante - Krzykawski, Michał (Polskie Towarzystwo Badań Kanadyjskich, 2013)
What I call “politics of migrant literature” summons up the sensible configuration of the community in which a kind of specific experience becomes visible. This article aims at cross-referring to an aesthetic dimension of the politics and it is mainly inspired by the works of Jacques Rancière, whose thought serves here as an interpretative tool to understand the transformation in the field of Québécois literature with the advent of the migrant literature (écriture migrante). I would like to show that this transformation was manifestly political.